PP34 Interventions to Promote Informed Consent for Invasive Healthcare Procedures: A Cochrane Systematic Review and Meta-Analysis. (10th September 2013) - Kelly, M J; Kinnersley, P; Phillips, K; Savage, K; Farrell, E; Morgan, B; Whistance, R; Lewis, V; Mann, M; Stephens, B L; Blazeby, J; Elwyn, G J; et al.
Abstract : Background: Informed consent is required before any surgery or invasive procedure is performed. Achieving ethically valid informed consent can be difficult: too little information may leave patients poorly informed and too much information may be overwhelming. As such interventions to promote information provision for informed consent are warranted. This study aimed to evaluate the impact of such interventions on a range of outcomes including patient knowledge, anxiety, and satisfaction. Methods: Medical databases were searched using keywords and subject headings (Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, PsycINFO). Reference lists of included studies were searched. Randomised controlled trials (RCTs) of interventions to promote informed consent for patients undergoing surgical or invasive procedures were included. Studies were dual-assessed. Random effects meta-analyses were conducted for all outcomes with sufficient information. Standardised mean differences summarised the output. Narrative synthesis was also performed. Results: 65 RCTs were identified from 12 countries. In total 9, 021 patients were randomised into these trials. Interventions employed various formats including written material, audio-visual tools and decision aids. Meta-analyses demonstrated statistically significant improvements in knowledge when measured immediately after interventions, shortly afterwards (between 24 hours and 15 days) and at a later date (15 days or more) (Immediate knowledge SMD 0.53 [95% CI 0.37, 0.69], I 2 73%; Short-term knowledge SMD 0.68 [0.42, 0.93], I 2 85%; Long-term knowledge SMD 0.78 [0.50, 1.06], I 2 82%). Satisfaction with decision making also improved (SMD 2.25 [1.36, 3.15], I 2 99% and decisional conflict was reduced (SMD -1.80 [-3.46, -0.14], I 2 99%). No statistically significant differences were found for generalised anxiety, anxiety with the consent process or satisfaction with the consent process (generalised anxiety SMD -0.11 [-0.35, -0.01], I 2 82%, anxiety with the consent process SMD 0.01 [-0.21, 0.23], I 2 70%; satisfaction with the consent process SMD 0.12 [-0.09, 0.32], I 2 76%). Conclusion: Interventions to promote informed consent consistently improve patient knowledge, an important prerequisite for informed consent and this is achieved without any significant harmful effects. Such interventions can thus be considered effective at promoting informed consent for invasive healthcare procedures. Further studies are necessary to investigate all aspects of informed consent as a unified concept.